HUBUNGAN KONSELING BERLANDASKAN “PEUMULIA JAMEE” (KEARIFAN LOKAL ACEH) - Zahra Nelissa; Sunaryo Kartadinata; Mamat Supriatna (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2022)
“Peumulia Jamee” is one of an important elements in the foundation of the counseling relationship in Aceh. This article contains about the study of